How Producers became Consumers (KULT_online, 2011)
In his book Leben als Konsum (Life as Consumption) Zygmunt Bauman investigates the phenomenon of modern consumption. He describes the evolution from a society of producers in the 19th century to today's society of consumers. The author conceives of the society of consumers as a network of human relationships, which has its basic nodes in the encounters of consumers and consumable goods. Bauman makes clear that in a society of consumers no one can become a subject without first becoming a consumable good oneself. The sociologist analyses the effects that behavioural patterns defined by consumption have on various aspects of society such as politics, social milieu structures or groups. Central to his considerations are hence topics like the changing of human relationships through structures of behavior that are formed according to measures of markets, the origins of resentment and rebellion against this way of life, and the question of the limits of the power of consumerism. The author x-rays culture of life in the present and re-interprets it in light of these topics.